PENGELOLAAN SEKOLAH KATEGORI MANDIRI STUDI SITUS SMA N 5 SEMARANG - HARDJANTO , TJATOER (2011)
SMA Negeri 5 Semarang is a national standard school indicated by National Education Department to represent Central Java province. This designation is based on the quality acquired so far. In the management the principal invites the entire society components to develop this school together; therefore a good cooperation between school and society is established. Based on the fact above, researcher aims to describe the management of basic education institution at SMA Negeri 5 Semarang, the purpose in details are 1) to describe the physical characteristics of SMA Negeri 5 Semarang, 2) to describe the school organization characteristics of SMA Negeri 5 Semarang, and 3) to describe the principal characteristics of working relationship with a teacher at SMA Negeri 5 Semarang. This is a qualitative research and ethnography strategy. The research location is SMA Negeri 5 Semarang. The data collection techniques are deep- interview, observation, and documentation study. The data analysis used is inductive analysis by applying three stages; data reduction, display data, and data verification. The data validity is done by triangulation technique. Research findings 1) the physical structure of SMA Negeri 5 Semarang consists of school building that is used for class rooms, office, library, laboratory, art workshop, and others, all functioned optimally, 2) the organization structure of the school consists of a) a headmaster as the school manager, educator, negotiator, and motivator for both teachers and students, b) a school committee as the liaison between society and school, the controller of finance expense, school consideration, and school programs supporter, c) school treasurer who manage school finance, there are two treasurers, one treasurer takes care of SPP fund and the other one takes care of government fund excluding SPP, and d) homeroom teacher has a responsible to the headmaster on the execution of assistance and monitoring, and has the authority to carry out any activity related with class assistance and monitoring; and 3) relationship the headmaster with teachers: a) the employment relationship, b) personal relationships.